Course and Outcomes of Acute Coronary Syndrome in the Presence of New Coronavirus Infection COVID-19 - L. S. Kokov; S. S. Petrikov; M. M. Pisankina; E. A. Dashevsky; K. A. Popugayev; M. V. Parkhomenko; I. M. Kuzmina; I. S. Babayan; K. I. Vorontsova; L. T. Khamidova; E. V. Klychnikova; S. P. Goncharov; et al. (Неотложная медицинская помощь, 2022)
Abstract We analyzed the clinical condition of patients with COVID-19 of varying severity, changes in instrumental and laboratory parameters, and assessed the impact of the severity of the course of a new coronavirus infection on the outcomes of acute coronary syndrome.AIM OF STUDY To study the mutual influence of acute coronary syndrome and the new coronavirus infection COVID-19 on the nature of the course and outcomes of the disease.Materia l and methods In March 21, 2020 – May 31, 2021, 3 625 patients were treated for COVID-19, including 131 patients with acute coronary syndrome due to COVID-19 disease. All patients underwent a number of studies: computed tomography of the chest, electrocardiography, echocardiography, monitoring of biomarkers of myocardial damage, diagnostic coronary angiography and, if necessary, intracoronary therapeutic intervention.Results Data on the distribution of patients with COVID-19 according to the presence or absence of ST segment elevation on the electrocardiogram and the degree of lung tissue damage, as well as information on mortality in these groups, are presented. The role of troponin I in the assessment of myocardial ischemia was analyzed. The direct dependence of its level on the volume of lung damage was found. The inverse relationship was shown between the degree of damage to the lung tissue and the indices of oxygen saturation in the blood. A poor prognostic value of low left ventricular ejection fraction in patients with COVID-19 disease has been described.Conclusions The development of acute coronary syndrome in the course of COVID-19 significantly worsens the prognosis of the disease, which requires the development of algorithms for providing medical care to patients in this category, as well as maximum vigilance in their treatment.